THE IMPACT OF FINANCIAL TECHNOLOGY ON BANKING PROFITABILITY IN INDONESIA - Muhammad Irham Ghiffary; Mahameru Rosy Rochmatullah (Journal of Applied Economics in Developing Countries, 2026)
This study investigates how Financial Technology (FinTech) influences banking profitability in Indonesia by comparing conventional and Islamic banks amid the country’s ongoing digital transformation. While FinTech adoption has grown rapidly in recent years, prior studies have mostly examined only one type of banking system, leaving limited evidence on whether digital financial services affect conventional and Islamic banks differently. To address this gap, this research uses a quantitative approach based on panel data from 180 observations of selected banks during the 2020–2024 period. FinTech adoption is represented by QRIS and mobile banking transactions, while profitability is measured using ROA, ROE, and NIM for conventional banks and NOM for Islamic banks. Multiple linear regression and classical assumption tests were used to analyze the data. The findings show that the impact of FinTech on profitability is not uniform across banking models. In conventional banks, QRIS significantly improves ROA and ROE, indicating that digital payment adoption helps improve transaction efficiency and financial performance. In Islamic banks, QRIS shows a broader impact and contributes more consistently to profitability, particularly in improving asset performance. Meanwhile, mobile banking tends to show weaker effects, suggesting that its financial benefits may take longer to materialize. These results highlight that the effectiveness of digital financial adoption depends on the operational characteristics of each banking system. This study adds comparative evidence from an emerging economy and suggests that regulators and banks should develop digital strategies that align with the specific needs of both conventional and Islamic financial institutions.